Order and stability of 2-point block backward difference method - Ijam H.M.; Ibrahim Z.B.; Senu N.; Suleiman M.; Rasedee A.F.N. (American Institute of Physics Inc., 2024)
This paper studied the order and stability of a 2-Point Block Backward Difference method (2PBBD) for solving systems of nonstiff higher order Ordinary Differential Equations (ODEs) directly. The method computes the estimated solutions at two points concurrently within an equidistant block. The integration coefficients that are used in the method are calculated only once at the beginning of the programming. The numerical results obtained compare the stability region and error growth rate of the proposed method with 2-Point Block Divided Difference method (2PBDD) and 1-Point Backward Difference method (1PBD). 2018 Author(s).